2010
DOI: 10.2174/1573406411006040184
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols in Physiological Concentrations Target Multidrug Resistant Cancer Cells

Abstract: Phytosterols have been proposed to act as potent anticancer agents. However the mechanism of their action has not been elucidated yet. Thus, the aim of our study was to determine whether plant sterols and their thermal processing products (in physiological concentration range) could influence the viability of cancer cells and thus could be considered as positive diet complements. Additionally we decided to study potential specificity of those natural compounds against cells showing high multidrug resistance. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Globally, these results confirm the apoptotic action of b-sitosterol, in agreement with our own results. Regarding cell cycle distribution, and in contrast to our findings, b-sitosterol (1 and 5 mM) did not induce significant changes in the cell cycle of MCF-7 cells at 24 h (Rubis et al 2010), possibly because of the lower concentrations and shorter incubation times involved.…”
Section: Breast Cancer Cellscontrasting
confidence: 99%
See 2 more Smart Citations
“…Globally, these results confirm the apoptotic action of b-sitosterol, in agreement with our own results. Regarding cell cycle distribution, and in contrast to our findings, b-sitosterol (1 and 5 mM) did not induce significant changes in the cell cycle of MCF-7 cells at 24 h (Rubis et al 2010), possibly because of the lower concentrations and shorter incubation times involved.…”
Section: Breast Cancer Cellscontrasting
confidence: 99%
“…Regarding the b-sitosterol standards, the growth inhibition percentages observed at 13 mM for 48 h are within levels recorded in previous studies (29-81%) with b-sitosterol at 16 mM tested between 1 and 5 days of incubation (Awad et al 2007(Awad et al , 2008Rubis et al 2010). On the other hand, it has been observed that b-sitosterol intake is associated to a greater probability of oestrogen receptor-positive (related to MCF-7) than oestrogen receptor-negative tumours, possibly explaining that MCF-7 cells may be more resistant to this compound (Touillaud et al 2005;Grattan 2013).…”
Section: Breast Cancer Cellssupporting
confidence: 86%
See 1 more Smart Citation
“…Cell cycle analysis and apoptosis detection was performed as previously described [19]. Briefly, after treatment with individual siRNAs targeting TERT and TERC subunits, cells were washed with 1 ml of PBS and fixed with 70 % ethanol overnight at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, researchers have been focusing on the effects of phytosterols toward various cancer cell lines and their implication in multidrug resistance [1921]. To date, several apoptotic pathways mediated by phytosterols have been proposed in cancer culture models such as the Ras/ERK and the PI3 K/Akt pathway [2226].…”
Section: Introductionmentioning
confidence: 99%